Pengaruh Penerapan Total Quality Management Terhadap Complain Pelanggan Pada Bagian Operasional PT Frisian Flag Indonesia - Subawa Subawa; Rudi Pamungkas (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Quality is the most basic thing in an industry, especially for the dairy and dairy products industry. Total Quality Management (TQM) is a system used to implement standards for quality improvement and is the company's commitment to quality development which involves all elements of employees so that they can compete globally. The purpose of this study was to find out how the influence of TQM implementation on customer satisfaction at the operational division of PT Frisian Flag Indonesia (FFI). PT FFI is a manufacturer of dairy-based nutritional products for children in Indonesia under the Frisian Flag brand, which is also known as Susu Bendera. The research method used is descriptive qualitative data analysis obtained through observation, interviews and documentation to be used to strengthen the data when comparing theory with implementation in the field. The results showed that the implementation of TQM at PT FFI had a 61% effect on reducing customer complaints. However, in practice, employee involvement must still be a concern because there are still employees who do not play an active role in implementing TQM, while the principles and components of TQM explain that the active involvement of all employees is required. Keywords: Customer, Total Quality Management, Influence